Metabolomics and Its Role in Inflammatory Bowel Disease: What Do We Know? - Tsonev, Nikolay; Zvezdov, Dimitar; Gashkova, D.; Andreeva, D.; Stefanova, M. (International Journal of Innovative Research in Medical Science, 2022)
Inflammatory bowel diseases comprise of ulcerative colitis and Crohn's disease, both of which have increasing incidence. Despite not having completely understood pathogenesis, genetic factors, environmental factors and microbiota are thought to play a role in a predisposed individual. Common symptoms include abdominal pain, diarrhea, fever, weight loss and rectal bleeding. Diagnosis is made by clinical, laboratory, endoscopic, radiologic and histologic examinations. Nevertheless, about 15% of patients do not have a definitive diagnosis. Metabolomics measures metabolites in a biological sample (feces, serum, urine, tissue and air) thereby having the potential to clarify disease pathogenesis and find new biomarkers, which will then aid in diagnosis, guide therapy and give prognosis.